Immunization Errors among Pediatrics Younger than 2 years - Al-lela, Omer Qutaiba B; Bahari, Mohd Baidi; Baderden, Sara K; Basher, Amina Y; Hamoodi, Hani Kareem (Journal of Pharmacy Practice and Community Medicine)
Objective: This study evaluated immunization compliance, immunization completeness, and vaccination errors frequency among Iraqi pediatric. Study design this study was restricted the analysis to types of vaccines administered before 2 years of age. A cohort study of 528 pediatrics born between 1st January 2003 and 31st Jun 2008 was selected. Immunization history of pediatric was collected retrospectively from pediatric immunization card. Immunization doses were classified to five types: Normal dose, early dose, missed dose, late dose, and extra dose. Pediatric who received all the immunization doses without any immunization dose errors was considered as complete immunization with full compliance. If the pediatric missed at least one immunization dose, this pediatric was considered partial immunization with noncompliance, and if this pediatric received at least one immunization dose error, this pediatric was considered complete immunization with noncompliance. Results Less than half of pediatric were considered as partial immunization with noncompliance. 3696 immunization doses must receive by 528 pediatric, 25.3% of doses were normal doses, 8.3% as an early doses, 13.6% as a missed doses, 47.5% of doses were late doses, and 5.3% as an extra doses. Conclusions Immunization errors occur frequently and leading to improper immunization compliance. This study recommended increasing effort to optimize childhood immunization.
Keywords: immunization; compliance; errors; pediatrics; two years